bahasa inggris - Pratama, R. Warsito Ayang; Dwianto, Agung Surya (Institut Pendidikan Tapanuli Selatan, 2025)
This study aims to examine in depth the role of transformational leadership in shaping and encouraging innovative work behavior of employees at PT Garuda Yamato Steel. In the context of the dynamics of the manufacturing industry that continues to grow and demands rapid adaptation to technological changes and global competition, transformational leaders play a strategic role in shaping a work climate that supports innovation. This research uses a qualitative approach with a case study method, through in-depth interviews with a number of key informants consisting of managers and employees from various departments. The findings show that the main dimensions of transformational leadership, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, contribute significantly to increasing the intensity and quality of innovative work behavior. Leaders who are able to inspire a shared vision, provide space for experimentation, and support individual capacity building, directly encourage the emergence of new ideas, creative work approaches, and courage in taking measured risks. In addition, this study found that the emotional connection between leaders and subordinates, built through trust and two-way communication, is an important foundation in shaping a work environment conducive to innovation. The context of organizational culture, hierarchical structure, and internal company dynamics also influence the effectiveness of transformational leadership style in triggering innovative behavior. The implications of this research point to the importance of developing transformational leadership competencies in organizations, especially at the managerial level, as part of a long-term strategy to maintain competitiveness through continuous innovation. This research also opens room for further exploration of the contextual influence of organizational culture on the effectiveness of leadership styles in the heavy industry sector.